Both Age and Disease Duration are Associated with Clinical Phenotype of Hori’s Nevus in Chinese: A Retrospective Analysis of 497 Cases - Zhong Y; Huang L; Yan T; Chen Y; Yang B; Man MQ (Dove Medical Press, 2021)
Yiping Zhong,* Lining Huang,* Tingting Yan, Yongjun Chen, Bin Yang, Mao-Qiang Man Aesthetic Department, Dermatology Hospital, Southern Medical University, Guangzhou, Guangdong 510091, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mao-Qiang Man; Bin YangDermatology Hospital, Southern Medical University, Guangzhou 510091, People’s Republic of ChinaTel +1415575-0539; +86-20-87257353Email mqman@hotmail.com; yangbin101@hotmail.comBackground: Hori’s nevus is a common pigmented disorder on the face, preferentially in females. The clinical features have not been well characterized.Aim: To characterize the clinical features of Hori’s nevus in Chinese adults.Subjects and Methods: Data were collected from files of patients who visited our hospital from 2015 to 2018. Age- and disease duration-related characteristics were analyzed.Results: A total of 497 patients, including 486 females and 11 males, were included in this analysis. One fifth of the patients had a family history of Hori’s nevus. Over 70% of patients were aged 21– 30 years. Age at onset was comparable between males and females (20.64 ± 1.01 vs 18.99 ± 0.24). Out of 497 subjects, 218 subjects (44%) displayed yellow-brown lesions while blue-brown lesions wwere observed in 103 subjects (21%). The rest (176 cases, 35%) showed slate-grey lesions. Involvement in the zygomatic area was observed in 496/497 subjects. Involvement in a single area accounted for 74% of patients, while two areas were involved in 19% of patients. The number of involved areas correlated positively with disease duration. However, the proportion of subjects with yellow-brown lesions correlated negatively with disease duration, while the proportion of subjects with slate-grey lesions correlated positively with disease duration. The proportion of subjects with lesions involving the lower eyelids, the root of the nose, the temple and the outer frontal area correlated positively with age.Conclusion: Hori’s nevus mainly involves the zygomatic area in subjects aged 21– 30 years. Lesion color is associated with age, age at onset, and disease duration.Keywords: Hori’s nevus, age, pigmentation